Separation technique of crude palm oil at clarification area via optimum parameters - Nurulhuda, Kasim (2009)
The purpose of clarification is to separate the oil from its entrained impurities such as water, cell debris, fibrous material and non oily solid (N.O.S). In this study, optimum parameter such as temperature, effect of impeller, residence time and separation technique of crude palm oil is at clarification stage is determined. By using correct separation technique and condition, mill can maximize oil production and reduce oil losses. In this experimental, CPO are heated at 50°C, 60°C, 70°C, 80°C, 90°C, 110°C and 120°C for optimum temperature determination using water shaker batch. Experimentally, the results proved that by using 95°C for heating, CPO took the shortest time for separation. Difference size beakers also tested while separation. As larger the surface area of beaker, shorter time is taken for CPO separation. Otherwise the volume of CPO is directly proportional to the separation time. The present of impeller also enhances the separation of oil and sludge thus reduced the oil content in underflow while the pure oil obtained is increased.